Experimental and computational studies on possibility of using glucose diazacrown cryptand as a carrier for anticancer drugs busulfan and lomustine - Anna Ignaczak; Marta Hoelm; Stanisław Porwański; Paweł Jóźwiak; Anna Krześlak (Scientific Reports)
Abstract Drug carriers play a very important role in pharmacy, especially in cancer therapy. Most drugs used in the treatment of cancer are characterized by poor solubility in water and lack of selectivity in their toxic effects on normal and cancer cells. Administration of the drug in the form of a complex with an appropriately selected carrier can significantly improve its therapeutic effect and reduce side effects. In this study, the possibility of using the cryptand L1, containing two diazacrown ethers and two saccharide groups, as a potential drug carrier is investigated. In order to determine whether it can form complexes with drugs, the cryptand L1 and its complexes with two anticancer drugs, busulfan (BSF) and lomustine (CCNU), were synthesized. Their selected structural and energetic properties were investigated using both experimental and computational methods. Additionally, water solubility and cytotoxicity tests were performed for all compounds. The measured 1H NMR spectra confirm that L1 forms complexes L1:BSF and L1:CCNU, the solubility of which in water appears to be much higher than that of the pure drugs. The results of DFT calculations made in water described with the implicit solvent model confirm high stability of L1:BSF and L1:CCNU and indicate that L1 forms with the drugs mainly non-inclusion complexes. However, additional tests with 20 H2O molecules explicitly included in the model suggest that both inclusion and non-inclusion forms can occur in a real solution. Cytotoxicity studies show that the macrocycle L1 is non-toxic towards both normal and cancer cells, and its complexes with drugs show greater selectivity towards cancer cells. Interestingly, while the cytotoxicity of the L1:BSF complex is stronger than that of pure BSF, the relationship is opposite in the case of L1:CCNU and CCNU. Therefore, L1 can be considered as a potential drug carrier, especially for those drugs that have weak activity on cancer cells.